Existence of Clemency as President Prerogative Right (Comparison Study of Indonesia with Countries of the World) - Fathudin .; Ahmad Tholabi Kharlie (Jurnal Cita Hukum, 2017)
The debate about the existence of clemency as a prerogative of the president stems from the understanding that the rights is coming independently from the authority and without any branches of power. In this context, the comparative study of the constitutional norms in some countries in the world related to the norm of clemency is important to read the tendency of other countries about clemency rules. This study shows that the constitutional norm of countries in the world basically has the same tendency in the application of clemency by the president; there is involvement of other branches of power. Some constitutions of the world call the recommendation, hearing, information, consultation, advice, in accord, concurrence (approval) and others. The involvement of other branches of power in the grant of pardon does not mean reducing the authority of the president (prerogative), but it has become a tendency in almost all modern states to embrace the system of government power within the framework of public accountability. The term prerogative of the president (absolute) in practice is no longer absolute and independent. Perdebatan sepuar eksistensi grasi sebagai hak prerogatif presiden berpangkal pada pemahaman yang menyebut bahwa suatu hak disebut sebagai hak prerogatif presiden jika kewenangan yang lahir dari hak tersebut bersifat khusus dan  mandiri tanpa adanya keterlibatan cabang kekuasaan lain. Dalam konteks ini, kajian perbandingan terutama terhadap norma konstitusi di beberapa negara di dunia terkait dengan norma tentang grasi menjadi penting untuk memotret kecenderungan yang dimiliki negara-negara lain dalam hal pengaturan tentang grasi. Kajian ini menunjukan bahwa norma konstitusi negara-negara di dunia pada dasarnya memiliki kecenderungan yang sama dalam penerapan pemberian grasi oleh presiden, yakni ada keterlibatan cabang kekuasaan lain. Beberapa konstitusi negara-negara di dunia menyebut keterlibatan tersebut dengan menggunakan ragam istilah seperti recomandation, hearing, inform, consultation, advice, in accordance, conccurance (persetujuan) dan lain-lain. Adanya keterlibatan cabang kekuasaan lain dalam mekanisme pemberian grasi bukan berarti mereduksi kewenangan presiden (hak prerogatif), tetapi memang menjadi kecenderungan hampir di semua negara-negara modern untuk menganut sistem pemerintahan yang berusaha menempatkan segala model kekuasaannya dalam kerangka pertanggungjawaban publik, sehingga istilah hak prerogatif presiden (sacara mutlak) dalam prakteknya tidak lagi bersifat mutlak dan mandiri. DOI: 10.15408/jch.v5i1.6574